Convergent evolution of type I antifreeze proteins from four different progenitors in response to global cooling - Laurie A. Graham; Peter L. Davies (BMC Molecular and Cell Biology)
Abstract Alanine-rich, alpha-helical type I antifreeze proteins (AFPs) in fishes are thought to have arisen independently in the last 30 Ma on at least four occasions. This hypothesis has recently been proven for flounder and sculpin AFPs, which both originated by gene duplication and divergence followed by substantial gene copy number expansion. Here, we examined the origins of the cunner (wrasse) and snailfish (liparid) AFPs. The cunner AFP has arisen by a similar route from the duplication and divergence of a GIMAP gene. The coding region for this AFP stems from an alanine-rich region flanking the GTPase domain of GIMAPa. The AFP gene has remained in the GIMAP gene locus and has undergone amplification there along with the GIMAPa gene. The AFP gene originated after the cunner diverged from its common ancestor with the closely related spotty and ballan wrasses, which exhibit similar gene synteny but lack AFP genes. Snailfish AFPs have also recently evolved because they are confined to a single genus of this family. In these AFP-producing species, the AFP locus does not share any similarity to functional genes. Instead, it is replete with repetitive DNAs and transposons, several stretches of which could encode alanine tracts with a dominant codon (GCC) that matches the bias observed in the AFP genes. All four known instances of type I AFPs occurring in fishes are independent evolutionary events that occurred soon after the onset of Northern Hemisphere Cenozoic glaciation events. Collectively, these results provide a remarkable example of convergent evolution to one AFP type.